The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/739461
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Dysregulation in Laryngeal Squamous Cell Carcinoma

Abstract: Laryngeal carcinoma is a common head and neck cancer with poor prognosis. Patients with laryngeal carcinoma usually present late leading to the reduced treatment efficacy and high rate of recurrence. Despite the advance in the use of molecular markers for monitoring human cancers in the past decades, there are still no reliable markers for use to screen laryngeal carcinoma and follow the patients after treatment. Epigenetics emerged as an important field in understanding the biology of the human malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 124 publications
1
21
0
Order By: Relevance
“…Many of these genes were already known to be involved in important functions, including apoptosis, the cell cycle, cell migration, and invasion (for reviews see refs. 28,29). Interestingly, a recent analysis has shown that a protein involved in cell adhesion (cadherin 11) is specifically methylated in metastases (30).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these genes were already known to be involved in important functions, including apoptosis, the cell cycle, cell migration, and invasion (for reviews see refs. 28,29). Interestingly, a recent analysis has shown that a protein involved in cell adhesion (cadherin 11) is specifically methylated in metastases (30).…”
Section: Discussionmentioning
confidence: 99%
“…1 The definite cause of laryngeal cancer is not yet determined, although some risk factors, such as tobacco and alcohol consumption, genetic and epigenetic alterations are believed to be linked with the development of this disease. 2,3 Telomerase reverse transcriptase (TERT) gene, which encodes the catalytic subunit of telomerase, has been demonstrated to be up-regulated in human cancers, contributing to carcinogenesis. 4 Recently, two recurrent somatic mutations (1,295,228 C>T and 1,295,250 C>T, hereafter named C228T and C250T, respectively) in the TERT gene promoter have been frequently reported in various human cancers, including melanoma (71%), thyroid cancer (22-51%), bladder cancer (84.6%) and glioblastoma (83.8%).…”
Section: Dear Editorsmentioning
confidence: 99%
“…Losses of the CDKN2A gene in our cohort are consistent with this fact. The lower frequency of copy number changes in the CDKN2A gene in our cohort when compared to the frequencies of the loss of the gene function may be explained by the fact that methylation of the gene is responsible for a significant proportion of the losses, as suggested by several studies …”
Section: Discussionmentioning
confidence: 63%